Peer Article Citation Impact: An Essay on Turkey-Addressed Information Science Articles - Köksal, Mücella Sena; Al, Umut (Information World, 2023)
This study examines Turkey’s contributions to information science and assesses the visibility of Turkey-addressed information science articles in the literature in terms of their citations. In other words, Turkey’s quantitative contributions to the information science literature are compared through citations, taking peer articles into account. The primary dataset used in the research was obtained through Web of Science and includes 600 Turkey-addressed information science articles. The findings of the study reveal that Turkey-addressed information science articles are produced by researchers from various disciplines. The conducted study can be seen as an attempt to establish a metric based on the provided data. Despite having many aspects open to criticism, the proposed metric allows each discipline to gauge its own effectiveness and position within its field based on the number of citations received compared to its peers. The conceptual background of the research, which relies on a previously completed postgraduate thesis, defines “peer articles” as articles published in the same issue of a journal, while “peer article citation impact” categorizes an article based on the number of citations it receives compared to its peers. To bring a different perspective on the subject and to contribute to the discussions to be made, especially in the context of the research evaluation literature, which is thought to have developed rapidly but not in a healthy way in Turkey recently, is among the targets of this study.